High isolation of single pole double throw switch with switchable resonator for wireless communications - Shairi, Noor Azwan (2015)
In wireless communication systems, Single Pole Double Throw (SPDT) switches are widely used in radio frequency (RF) front-end system to support transmit and receive modes switching for Time Division Duplex (TDD)communication. High isolation between transmitter and receiver in the RF front-end is one of the key parameters in SPDT switch design, especially for high power applications such as a base station and wireless infrastructure. Therefore, this research work introduced a new high isolation of SPDT discrete switch design using switchable resonator that includes minimum number of PIN diodes or produce absorptive feature. The microstrip resonators such as a transmission line stub, radial stub, parallel coupled line and ring were selected in this research work. By analyzing a mathematical model of simplified SPDT switch with resonator, a high isolation could be achieved due to a bandstop response of the resonators. These resonators were able to reconfigure between bandstop and allpass or bandstop and bandpass responses to support transmit and receive modes switching. The proposed SPDT switches with switchable resonator were demonstrated for the applications of Time Division Synchronous Code Division Multiple Access (TDSCDMA) in 2 GHz band and Worldwide Interoperability for Microwave Access (WiMAX) and Long Term Evolution (LTE) in 3.5 GHz band. Results showed that isolation of more than -25 dB was achieved in the SPDT discrete switch design using these four types of switchable resonators and suitable for high power application with 1 Watt and 10 Watt transmit output power. Despite high isolation performance, the proposed SPDT switches (with transmission line stub and radial stub resonators) used a minimum number of PIN diodes compared to conventional multiple cascaded switches technique. Meanwhile, the proposed SPDT switches (with parallel coupled line and ring resonators) produced high isolation with absorptive feature without additional circuit components.